A comparison study of the commercial solar systems materials and its applications - Cheah, Chee Pei (2009)
Solar Energy Materials and solar cells are intended as a vehicle for the dissemination of research results on materials science and technology related to photovoltaic, photothermal and photoelectrochemical solar energy conversion. Materials Science is taken in the broadcast possible sense and encompasses physics, chemistry, optics, materials fabrication and analysis for all types of materials. This project is carried out with the purpose to do a comparison study of the commercial solar cells and materials, measurement of solar panels performance, selection of solar cells and materials, integration of the proposed solar cells and materials to the commercial photovoltaic system and discussion of the future solar cells development. The ultimate objective of the project is to select a photovoltaic cell materials from the commercial market with better efficiency and yet lower cost. Hopefully the project would provide a better understanding of the photovoltaic systems materials and could have contributed the effort in promoting the application of the green house energy material s especially in our tropical countries. Different test methods are conducted on the commercial photovoltaic materials. The results shows that the efficiency of the CIGS solar PV materials shows up to 16% and it has the most stable output power as compare with the rest. Through the detail analysis, power losses and factors are analysed, it shows that the efficiency can be further improve by minimising the ohmic losses and other external factors. The CIGS application is growing rapidly due to its consistency performance, flexibility and cheaper price.